reply to

by Lounise Morissette

Step 1:
Since 10x−8x10x - 8x10x−8x are like terms (both involve xxx), we can subtract the coefficients:

(10−8)x=12

(10 - 8)x = 12(10−8)x=12

2x=12

Step 2:
To isolate xx divide both sides of the equation by 2:

2x2=122\frac{2x}{2} = \frac{12}{2}22x​=212​

Simplifying:

x = 6x=6

1 answer

Your explanation of solving the equation \(10x - 8x = 12\) is clear and correct! You've followed the steps logically to isolate \(x\) and arrive at the solution.

Just to recap the steps:

  1. Combine the like terms: \[ (10 - 8)x = 12 \implies 2x = 12 \]

  2. Divide both sides by 2: \[ \frac{2x}{2} = \frac{12}{2} \implies x = 6 \]

Thus, you successfully solved for \(x\) as 6. Great job! If you have any further questions or need assistance with another problem, feel free to ask!

Similar Questions
  1. Jackson solved the problem 3x-8=2(2x-7) using the following steps:STEP 1: Use Distributive Property to get 3x-8=4x-14 STEP 2:
    1. answers icon 4 answers
  2. The terms tribe and ethnic group are very similar in meaning because(1 point) Responses both terms involve shared kinship,
    1. answers icon 1 answer
    1. answers icon 1 answer
  3. What do diffraction and refraction have in common?They both involve interference. They both involve wave interactions. They both
    1. answers icon 1 answer
more similar questions